Bacterial expression, purification and folding of exceptionally hydrophobic and essential protein: Surfactant Protein-B (SP-B) - Tadiwos Asrat; Donna Jackman; Valerie Booth (PLoS ONE, 2025)
Lung Surfactant Protein B (SP-B) is essential for life. It is thus striking that, to this point, no method for making the full-length protein has been published and consequently we lack detailed understanding of SP-B’s basic structure-function relationships, as well as an inability to make it for clinical use. The major challenge in producing SP-B lies with its exceptionally hydrophobic nature. In this work, we present a method to produce recombinant SP-B in bacteria that can be used to make the full-length protein as well as the product focused on here, which is a construct lacking the N-terminal 7 residues, rSP-B (Δ7NTC48S-SP-B-6His). The construct is produced as a fusion to Staphylococcus nuclease A (SN) in Escherichia coli C43 cells, a strain known to promote production of toxic and membrane recombinant proteins. After cleavage from SN, rSP-B is folded on column and then exchanged into the lipid or detergent system of choice. rSP-B prepared in this way exhibits the correct secondary structure and demonstrates surface activity. The yield obtained is 0.3 mg of purified rSP-B (Δ7NTC48S-SP-B-6His) per liter of initial bacterial culture. We expect this method for producing SP-B will be valuable in enabling basic research into SP-B’s mechanisms, as well as possibly facilitating the inclusion of SP-B in lung surfactant formulations to treat common and frequently fatal lung conditions and in lung surfactant-based drug delivery.